Ambiguitas, Inkonsistensi, dan Pengabaian Kepentingan Lokal dalam Kebijakan Penyiaran Televisi di Indonesia - Rahayu Rahayu (Jurnal Komunikasi)
This research explains the policy and practices of local television broadcasting in Indonesia post-reformation era (2002-2017). Researcher connect the policy and practices with the the localism principles in communication policy as well as with the opinion of the local people who had interest over the conduct of local television broadcasting. The issue of local television broadcasting becomes the focus of the research as it is one of the main agenda during Indonesia broadcasting reformation order to build a national broadcasting system which could guarantee the creation of a just, and balanced national information order to protect the diversity of Indonesian people and the effective conduct of local autonomy. The study covered analysis on broadcasting regulation documents, interviews on a number of stakeholders in the local broadcasting, as well as conducted observations in three areas, which are Yogyakarta, Denpasar and Makassar. The study results show that policy and television broadcasting practice in local areas are coloured with ambiguity and inconsistency in regulation, deviation between regulation and practice, as well as negligence over the local people interest. The manifestation of these problems are reflected on the issue of local broadcasting station presence, local contents, and the position of local regulator.